Medication history assessment in research: A randomized controlled trial comparing tablet‐based (eMedHAT) versus structured interview (MedHAT). Issue 12 (5th October 2018) - Green, Jody L.; Anderson, Victoria; Dart, Richard C.; Heard, Kennon
Abstract: Purpose: Accurate capture of medication use is important for high quality research. For epidemiologic studies, medication histories are the most common measure of exposure when trying to identify associations between medications and outcomes. Concomitant medications can alter the efficacy or safety of study drugs in clinical trials. However, there are few studies evaluating the accuracy and efficiency of methods to collect these histories. The objective of this study is to compare the accuracy of medication histories collected by structured interview to histories captured using a tablet‐based application. Methods: This was a randomized controlled trial. Subjects were instructed to record all prescription medications, non‐prescription medications, vitamins, and dietary supplements in a diary for 30 days. At the end of the diary collection, subjects were randomized to providing a medication history during a structured interview by a trained research assistant (MedHAT) or using a tablet‐based application (eMedHAT). The accuracy of these histories was compared using an adjusted analysis. We also measured the duration of the history collection and data entry. Results: A total of 111 subjects were in the MedHAT group and 109 subjects were in the eMedHAT group. Recall of medications for the 30‐day period was similar for MedHAT and eMedHAT (76.9% versus 75.2%, respectively). The total time required for researchers and subjects for history collection and data entry was 16 minutes shorter for the tablet‐based method. Conclusions: Tablet‐based medication histories were as accurate as histories obtained by research assistants and required less time for the researcher.